2004
DOI: 10.1002/ctpp.200410102
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Baffled Probe for Measurements of Oscillations in Magnetized Plasma

Abstract: Key words Electric probe, magnetized plasma, space potential and temperature oscillations. PACS 52.70.-m A baffled probe for distinguishing the oscillations of space potential and temperature in magnetized plasma is tested. The probe consists of a tungsten wire tip, oriented perpendicular to the magnetic field, that is partially shielded by ceramic baffles (masks). The probe works under the condition that the electron Larmor radius is much smaller than the probe radius, and the ion Larmor radius is comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 19 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…As it was shown in Ref. [14], the probe floating potential oscillationsṼ fl can be represented asṼ ). For such isolation, a cluster of at least four probes is required.…”
Section: Design Of Baffled-probe Clustermentioning
confidence: 93%
See 2 more Smart Citations
“…As it was shown in Ref. [14], the probe floating potential oscillationsṼ fl can be represented asṼ ). For such isolation, a cluster of at least four probes is required.…”
Section: Design Of Baffled-probe Clustermentioning
confidence: 93%
“…As it was shown in Ref. [14] Subtracting the fluctuating floating potentialsṼ fl (t) obtained from two probes in an array yields a quantity that reflects both the electric field component along the array and the propagation of the temperature fluctuation in the array direction. The effect of the propagating temperature fluctuations on this quantity can be minimized by orienting the probes so that I sat e /I sat i ≈ 1 in which case the quantity can be interpreted as the electric field.…”
Section: Design Of Baffled-probe Clustermentioning
confidence: 95%
See 1 more Smart Citation
“…Demidov et al 2,8,9 appears to be the first to suggest using similar probes in a floating regime for measurements of Ṽ s , electric field Ẽ s , and T i in a magnetized plasma, which dramatically increases temporal resolution with respect to fast sweeping probes, and this paper summarizes its potential and achieved outcomes. It was demonstrated that, for plasmas with Maxwellian charged particle distributions, if the probe electron saturation current I sat e is approximately equal to the ion saturation currant I sat i , then the probe floating potential For practical measurements of Ṽ s and Ẽ s the plug probes 10 and the baffled probes 11 have been used.…”
mentioning
confidence: 99%
“…Later a novel ion-sensitive probe, which is basically a combination of the Katsumata probe and ion energy analyzer, was used by Ochoukov et al 14 Measurements of T i have not been reported yet, but it is demonstrated that appropriate regime when I sat i ӷ I sat e is possible. 9 The principles of operation of all these probes are similar and based on the dependence of the voltage drop in the plasma-probe sheath on the direction of the local magnetic field. When the magnetic field is parallel to the probe surface, the electron-repelling sheath can be significantly reduced as the magnetic field also impedes the cross-field electron flow and therefore, a smaller sheath voltage is needed to maintain the zero current balance to the floating probe.…”
mentioning
confidence: 99%